تنفيذ الميزانية العامة للدولة - باجي حبيبة (جامعة المسيلة, 2021)
- جاءت هذه المذكرة لدراسة تنفيذ الميزانية العامة للدولة و ذلك بتقديم اإلطار العام لميزانية الدولة، إضافة إلى عرض اإلطار التنظيمي للميزانية العامة في الجزائر ومبادئها ووثائقها، من ثم مرحلة تنفيذ الميزانية العامة للدولة،و يقصد بها وضع بنودها المختلفة مو ضع التنفيذ. وتختص بها السلطة التنفيذية، و تمثل انتقال الميزانية العامة من مجال التقدير والتوقيع للسنة المقبلة إلى حيز التطبيقي . فتتولى الحكومة تحصيل و جباية اإليرادات الواردة المقدرة في الميزانية، كما تتولى اإلنفاق على األوجه المدرجة في الميزانية. ولضمان تنفيذ الميزانية في األوجه المحددة لها، فقد اقتضى األمر إيجاد وسائل مختلفة لمراقبة الميزانية للتأكد من مراعاة واحترام المكلفين بالتنفيذ كافة القواعد المالية أثناء ممارستهم لوظائفهم، والهدف من الرقابة هو التأكد من أن تنفيذ الميزانية قد تم على الوجه المحدد وو فق السياسة التي وضعتها السلطة التنفيذية و إجازتها من طرف السلطة التشريعية، وتأخذ الرقابة على تنفيذ الميزانية عدة صور مختلفة. الكلمات المفتاحية: الميزانية العامة للدولة، تنفيذ الميزانية ، رقابة التنفيذ. Abstract This memorandum came to study the implementation of the state’s general budget by presenting the general framework for the state’s budget, in addition to presenting the organizational framework for the general budget in Algeria, its principles and documents, and then the stage of implementing the state’s general budget, intended to put its various items into effect. It is the responsibility of the executive authority, and it represents the transition of the general budget from the field of estimation and signature for the coming year to the practical one. The government collects and collects the revenues estimated in the budget, as well as spending on the aspects listed in the budget. In order to ensure the implementation of the budget in the aspects specified for it, it has been necessary to find various means to monitor the budget to ensure that all financial rules are observed and respected by those charged with implementation while exercising their functions, and the goal of control is to ensure that the implementation of the budget is carried out in the specified manner and in accordance with the policy set by the executive authority and It is approved by the legislative authority, and oversight over the implementation of the budget takes several different forms. Key words: the state's general budget, budget execution, implementation oversight.
Keywords: الميزانية العامة للدولة، تنفيذ الميزانية ، رقابة التنفيذ